2023
DOI: 10.1021/acs.est.2c08141
|View full text |Cite
|
Sign up to set email alerts
|

Carbocatalysts for Enhancing Permanganate Oxidation of Sulfisoxazole

Abstract: Permanganate (Mn(VII)) is extensively applied in water purification due to its stability and ease of handling, but it is a mild oxidant for trace organic contaminants (TrOCs). Hence, there is significant interest in strategies for enhancing reaction kinetics, especially in combination with efficient and economical carbocatalysts. This study compared the performance of four carbocatalysts (graphite, graphene oxide (GO), reduced-GO (rGO), and nitrogen-doped rGO (N-rGO)) in accelerating sulfisoxazole (SSX) oxidat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 67 publications
(128 reference statements)
0
3
0
Order By: Relevance
“…To enhance the removal efficiency of mZVI-A, it is possible to accelerate its electron transfer process by incorporating external carbon materials. Various carbon materials are available for this purpose, including biochar, carbon nanotubes, , graphene oxide, , among others.…”
Section: Resultsmentioning
confidence: 99%
“…To enhance the removal efficiency of mZVI-A, it is possible to accelerate its electron transfer process by incorporating external carbon materials. Various carbon materials are available for this purpose, including biochar, carbon nanotubes, , graphene oxide, , among others.…”
Section: Resultsmentioning
confidence: 99%
“…Although the triplet peak signal corresponding to the TEMP-1 O 2 adducts was detected, it appeared that 1 PMSO could be targeted to react with high-valent metals to form PMSO 2 leading to PMSO depletion. 71 Therefore PMSO was selected as a probe for high-valent Mn to find out whether high-valent Mn contributes to As(III) oxidation, and the experimental results are shown in Fig. S17.…”
Section: As(iii) Oxidation Mechanismmentioning
confidence: 99%
“…12,13 For instance, Zhang et al focused on the ruthenium-loaded catalysts and found that they could promote the reaction between Mn(VII) and TrOCs by generating higher metallic valent states (e.g., Ru(VI) and Ru(VII)). 14,15 Recent reports demonstrated that carbonaceous catalysts (e.g., carbon nanotubes, 16 graphite, 17 graphite oxide, 18 reduced graphene oxide, 19 and biochar 20,21 ) could enhance the degradation of TrOCs by Mn(VII) via mediating the electron transfer and/or generating reactive manganese species (RMnS) (e.g., Mn(VI) and Mn(V)). Some soluble redox mediators (e.g., 2,2′-azino-bis(3-ethylbenzothiazoline)-6-sulfonate (ABTS) and 9-azabicyclo[3.3.1]nonane N-oxyl (ABNO)) can act as the electron shuttles to catalyze the TrOC degradation by Mn(VII).…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, various strategies have been proposed to enhance the oxidation of TrOCs by Mn­(VII), where different mechanisms are involved. , For instance, Zhang et al focused on the ruthenium-loaded catalysts and found that they could promote the reaction between Mn­(VII) and TrOCs by generating higher metallic valent states (e.g., Ru­(VI) and Ru­(VII)). , Recent reports demonstrated that carbonaceous catalysts (e.g., carbon nanotubes, graphite, graphite oxide, reduced graphene oxide, and biochar , ) could enhance the degradation of TrOCs by Mn­(VII) via mediating the electron transfer and/or generating reactive manganese species (RMnS) (e.g., Mn­(VI) and Mn­(V)). Some soluble redox mediators (e.g., 2,2′-azino-bis­(3-ethylbenzothiazoline)-6-sulfonate (ABTS) and 9-azabicyclo[3.3.1]­nonane N -oxyl (ABNO)) can act as the electron shuttles to catalyze the TrOC degradation by Mn­(VII). , Our group showed that several ligands (e.g., pyrophosphate, EDTA, and humic acid) could stabilize Mn­(III) species formed in situ upon Mn­(VII) reduction, resulting in a significantly enhanced oxidation of bisphenol A at a relatively low solution pH of 5.0–6.0 .…”
Section: Introductionmentioning
confidence: 99%